Tinjauan Hukum Ekonomi Syariah Terhadap Pemberian Uang Muka Pada Money Changer (Studi Kasus PT. Hamdalah Kab. Jember) - Halili Halili; Selfiatun Hasanah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
The transaction of buying and selling currencies is made in the form of transactions whose legal status in the view of Islamic teachings differs from one form to another. Buying and selling foreign currency in Islam the name is Al Sharf which is a sale of currency, where money is used as the object of exchange. Based on the above background, it can be formulated into several problem formulations (1) how the practice of money changer in PT. Hamdalah Kab. Jember? (2) how the review of sharia economic law against the practice of money changer in PT. Hamdalah Kab. Jember. The method used in this research is a qualitative study that uses descriptive analysis. The type of data used in this study is qualitative data. Data collection techniques used are through interviews and literature study. Based on the results of the research concluded that the practice of buying and selling money changer transactions in PT. Hamdalah Kab. Jember that uses the system of giving advances there is a mismatch. This is not in accordance with the provisions of the existing theory that in the sale and purchase of money changer does not need any down payment, but even if the practice in the field contrary to the theory does not necessarily punished harom, but this contract can be directed to the sale and purchase of salam contract. While giving a period of time in money changer transactions may be done if it becomes an unavoidable need (lil hajah) urfnya about 2-7 days. Keywords: Sharia Economic Law, Money Changer, Al Sharf and Foreign Currency Sale and Purchase.